Bronchoplatic surgery in the treatment of patients with nonsmall cell lung cancer - A. A. Aksarin; M. D. Ter-Ovanesov; S. M. Kopeyka (Сибирский онкологический журнал)
Aim. To study the effect of organ-preserving bronchoplastic surgery on long-term treatment outcomes of patients with non-small cell lung cancer (NSCLC ).Material and Methods. The long-term results of surgical treatment of 740 patients with stage I–III NSCLC , who were treated in Ugra from 2002 to 2015, were analyzed. Lobectomy and bilobectomy were performed in 477 patients, and pneumonectomy was performed in 263 patients. Thirty-two patients underwent bronchoplastic lobectomy and bilobectomy. Intraoperative pathological frozen sections of lymph nodes (# 12) of the remaining lobe of the lung were examined in all patients. If metastases in these lymph nodes were not detected, we performed bronchoplastic lobectomy. If metastases in lymph nodes of the remaining lobe were detected, we performed pneumonectomy. The median age of the patients (only male patients) was 55.3 ± 9.9 years. In 19 (59.4 %) patients, sleeve resections were performed on the right side and in 13 (40.6 %) patients, these resections were performed on the left side. There were 15 bronchoplastic lobectomies of type A, 9 of type B, 4 of type C, and 4 of type D. Sleeve resection of the pulmonary artery was performed in 4 patients. In 16 cases (50.0 %), there were no regional metastases (pN0). In 10 (31.3 %) cases, there was pN1, in six – pN2 (18.7 %).Results. There were no cases of postoperative death. Late complications (asymptomatic bronchial stenosis) occurred in 3 (9.4 %) patients. Long-term treatment outcomes were better in patients who underwent organ-preserving bronchoplastic surgery than in patients who underwent pneumonectomy. Median survival was 66 months after bronchoplastic lobectomies and 34 months after pneumonectomies (p=0.01). The 5- and 10-year survival rates in patients who underwent bronchoplastic lobectomies were 52.9 % and 36.2 %, respectively. The corresponding values in patients who underwent pneumonectomies were 38.0 % and 31.9 %, respectively.Conclusion. Organ-preserving bronchoplastic surgery compared to pneumonectomy does not worsen long-term outcomes in patients with NSCLC .